2018
DOI: 10.1111/jcpt.12794
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety between febuxostat and allopurinol in early post-renal transplant recipients with new onset of hyperuricemia

Abstract: Summary What is known and objective Febuxostat and allopurinol are xanthine oxidase inhibitors for urate‐lowering therapy. The efficacy and safety of febuxostat and allopurinol have been mostly reported in hyperuricemia patients with normal renal function. Here, we aimed to compare the effects of these two drugs in early post‐renal transplant recipients, focusing on evaluating the urate‐lowering effect and recovery of allograft renal function. Methods A retrospective cohort study was performed in early post‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Even though the Egger test for our main primary outcome of eGFR at end of study was not significant ( P > .05), a funnel plot for serum UA of the included studies in this meta‐analysis suggested two studies rendering a large effect estimate that lay outside the pseudo 95% CI (Figure ).…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…Even though the Egger test for our main primary outcome of eGFR at end of study was not significant ( P > .05), a funnel plot for serum UA of the included studies in this meta‐analysis suggested two studies rendering a large effect estimate that lay outside the pseudo 95% CI (Figure ).…”
Section: Resultsmentioning
confidence: 70%
“…Sample sizes of the seven studies ranged from 15 to 124 participants. Three studies were conducted in China, two in Japan, one in Korea, and one in Spain . There were three studies that had no control group .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations